2021
DOI: 10.1080/21655979.2021.1956671
|View full text |Cite
|
Sign up to set email alerts
|

Lysophosphatidylcholine promotes intercellular adhesion molecule-1 and vascular cell adhesion molecule-1 expression in human umbilical vein endothelial cells via an orphan G protein receptor 2-mediated signaling pathway

Abstract: Chang (2021) Lysophosphatidylcholine promotes intercellular adhesion molecule-1 and vascular cell adhesion molecule-1 expression in human umbilical vein endothelial cells via an orphan G protein receptor 2-mediated signaling pathway, Bioengineered, 12:1, 4520-4535,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 55 publications
(62 reference statements)
0
6
0
Order By: Relevance
“…Icam1 (Inter cellular adhesion molecule-1) is an adhesion receptor found in leukocytes and endothelial cells. Previous reports have shown that upregulation of both Icam1 and Vcam1 had a positive correlation with the destruction of capillaries and tubular cells in kidney rejection ( Vitoria et al, 2019 ; Zhang et al, 2021 ). On one hand, adhesion molecules serve as infiltration mediators; on the other hand, adhesion molecules may also be a costimulatory signal for T-cell activation by antigen-presenting cells ( Wang et al, 2018 ).…”
Section: Discussionmentioning
confidence: 80%
“…Icam1 (Inter cellular adhesion molecule-1) is an adhesion receptor found in leukocytes and endothelial cells. Previous reports have shown that upregulation of both Icam1 and Vcam1 had a positive correlation with the destruction of capillaries and tubular cells in kidney rejection ( Vitoria et al, 2019 ; Zhang et al, 2021 ). On one hand, adhesion molecules serve as infiltration mediators; on the other hand, adhesion molecules may also be a costimulatory signal for T-cell activation by antigen-presenting cells ( Wang et al, 2018 ).…”
Section: Discussionmentioning
confidence: 80%
“…These cells were cultured and grown in 2% serum endothelial growth media (EGM2) (Lonza, Switzerland) supplied with FBS (10%, v/v) and antibiotics at 37°C in a humidified 5% CO 2 incubator. Cells were exposed to ox-LDL (100 µg/ml) (Sigma-Aldrich, USA) in the inclusion or exclusion 1 and 2 μM Rotigotine (Topscience, Shanghai, China) for another 24 hours [ 23 ].…”
Section: Methodsmentioning
confidence: 99%
“…In ECs, ox-LDL causes endothelial adhesion genes implicated in atherogenesis and endothelial dysfunction such as ICAM-1, monocyte chemoattractant protein-1 (MCP-1), and VCAM-1 to be expressed [ 22 , 23 ]. Although macrophages normally express few receptors for normal LDL, they can take up ox-LDL by ways of scavenger receptors.…”
Section: Introductionmentioning
confidence: 99%
“…no. sc-5203; Santa Cruz Biotechnology, Santa Cruz, CA, USA) were visualized through strengthened the chemiluminescence (ECL, Amersham Biosciences Corp, NJ, USA), and the analysis of relative band intensity was conducted with ImageJ version 1.46 (National Institutes of Health, Bethesda, MD, USA) [ 15 ].…”
Section: Methodsmentioning
confidence: 99%